2014
DOI: 10.1371/journal.pone.0097993
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Management Practices of Private Practitioners in Pune Municipal Corporation, India

Abstract: BackgroundPrivate Practitioners (PP) are the primary source of health care for patients in India. Limited representative information is available on TB management practices of Indian PP or on the efficacy of India’s Revised National Tuberculosis Control Programme (RNTCP) to improve the quality of TB management through training of PP.MethodsWe conducted a cross-sectional survey of a systematic random sample of PP in one urban area in Western India (Pune, Maharashtra). We presented sample clinical vignettes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 3 publications
1
27
1
Order By: Relevance
“…In this study almost all the patients managed at the public and private DOTS facilities did sputum smear microscopy before commencement of anti-TB treatment. This is similar to findings from studies from Nigeria and elsewhere [9] [11] [17] [18]. However other studies from another part of Nigeria and Ethiopia showed that some of the patients treated at the public and private DOTS facilities did not do smear microscopy before initiation of anti-TB treatment [7] [19].…”
Section: Discussionsupporting
confidence: 88%
“…In this study almost all the patients managed at the public and private DOTS facilities did sputum smear microscopy before commencement of anti-TB treatment. This is similar to findings from studies from Nigeria and elsewhere [9] [11] [17] [18]. However other studies from another part of Nigeria and Ethiopia showed that some of the patients treated at the public and private DOTS facilities did not do smear microscopy before initiation of anti-TB treatment [7] [19].…”
Section: Discussionsupporting
confidence: 88%
“…21,22,24 The present study shows that 70% of the practitioners were referring their patients instead of treating them. This may be due to lack of diagnostic or treatment modalities or services or ignorance about the services provided by RNTCP.…”
Section: Discussionmentioning
confidence: 61%
“…The proportion is 80% in the present study, 100% in Vadodara, 90% in a study conducted in Pune by Bharaswadkar et al, and 85.71% in Jamnagar. 21,22,24 The number was only 40% in a study at Chandigarh by Thakur et al 25 The overuse of X ray as a diagnostic modality invariably increases the cost of Tuberculosis management that leads to decreased patient compliance, added to the harmful effects of unnecessary X ray exposure, which eventually leads to increased Tuberculosis burden in the society.…”
Section: Discussionmentioning
confidence: 99%
“…What is the usefulness of the result of mid CP follow-up sputum smear examinations in declaring outcomes and guiding further management of smear positive TB patients under RNTCP?Yes [32]9. Do private practitioners who are exposed to RNTCP involvement efforts report better diagnostic and treatment practices for TB than practitioners who are not exposed with regards to International Standards of TB Care (ISTC)?Yes [42]10. Are there any differences in TB management practices by private practitioners in Vishakhapatnam as compared to ISTCYes [41]11.…”
Section: Implementation Of Operational Research Training Coursesmentioning
confidence: 99%
“…Several studies at the same time started highlighting increasing levels of drug-resistant TB from various parts of the country, resulting mainly from inappropriate diagnosis and anti-TB treatment. OR studies undertaken during the same time period in two different cities of the country indicated deficiencies in the private health care providers’ knowledge and practices pertaining to TB diagnosis and treatment [41,42]. At the global level, WHO stepped-up the process of tracking the ‘missing TB cases’ (cases that are not notified to the national TB programmes) and requested all high TB burden countries to enhance their disease surveillance process [43].…”
Section: Contribution Of or To Policy And Practicementioning
confidence: 99%